Determination Of The Role Of Venture Capital Companies On Economic Development In Indonesia - Ratih Hastasari; Suharini (Sean Institute, 2023)
This study aims to describe the activities of venture capital companies in Indonesia as a non-bank financial institution. Venture Capital is unique in investing activities by participating in managing and supervising the investee so that its role in the progress of the Indonesian economy cannot be ignored. The research analysis uses qualitative descriptive statistical methods by observing and describing data collected online through the official websites of the OJK, other government agencies, and also other trusted national news websites. From the description of the data obtained, it shows that the role of venture capital in funding start-ups and MSME-scale businesses has a fairly important role in its development. The results also show that financing and investment activities carried out by venture capital are not evenly distributed, activities based on location are still focused on DKI Jakarta and provinces on the island of Java. The proportion of funding obtained by business units outside Java Island is only 15.04%, while DKI Jakarta is 37.58% of the total venture capital funding.